Determination of Protein Content by Spectrophotometric Method and Fat Content by Soxhletation Method on Purple Kopek Eggplant and Green Kopek Eggplant - Kartika Hasan (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
The type of research is quantitative research which is concerned with determining how much certain substances are contained in a sample. The formulation of the problem in this study is how much protein and fat levels are contained in the green kopek green eggplant kopeksangegg plant. The study was conducted to determine how many grams of protein and fat content in purple kopek eggplant and green kopek eggplant samples. With a spectrophotometric method (Lowry) for the determination of protein content and one method of hot extraction is the soxhletation method for the determination of fat content. The results showed that the protein content in 50 g of eggplant purple kopek was 0.0323 g and 50 g eggplant green kopek was 0.0375 g. The fat content in 10 grams of eggplant purple kopek is 0.1794% and 10 grams of eggplant green kopek is 0.1612%. Based on the results of the research that has been carried out, it was found that the protein content of eggplant kopek did not meet the DKBM standard, namely 1.4-2 g in a sample of 100 g. While the standard fat content obtained by DKBM is 1.1 g in a sample of 100 g.